PROTON-PUMP INHIBITOR USE AND POTENTIAL DRUG INTERACTIONS IN OUTPATIENTS - Syafhan, Nadia Farhanah; Augustine, Maulidya; Ramadhani, Uci; Hersunaryati, Yetti (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to evaluate the use and potential drug interactions of proton-pump inhibitor (PPI) in outpatients. Methods: This study is a retrospective descriptive analysis of prescriptions and medical records from outpatients in Gatot Soebroto Army Hospital selected by purposive sampling who received PPI with one or more other drugs from July to December 2015. The analysis was conducted on 400 prescriptions from 192 patients. Results: Data showed that 100% of the PPI therapy utilized was appropriate for the patients' condition, 79.00% was appropriate for the indication, 79.00% was appropriate for the dosage, 79.00% had an appropriate administration duration, and 83.75% was given the appropriate drug. The potential of PPI interactions with other drugs was found in 324 prescriptions (81.00%) from 475 cases. Of all the cases, 42 were considered major interactions, 138 were moderate interactions, and 295 cases had minor interactions. There were 14 drugs that could potentially interact with PPI, such as mycophenolate mofetil, clopidogrel, cilostazol, warfarin, iron, levothyroxine, propranolol, cyclosporine, simvastatin, atorvastatin, cyanocobalamin, sucralfate, theophylline, and antacids. Conclusion: PPI use in outpatients at the Gatot Soebroto Army Hospital was not entirely appropriate and had a large number of potential drug interactions with concurrent drugs.